2021
DOI: 10.1002/med.21785
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and cardiovascular protective effects of Huang‐Qi (Astragali Radix)

Abstract: Huang‐Qi (Astragali Radix) is an herbal tonic widely used in China and many other countries. It is derived from the roots of Astragalus membranaceus and A. membranaceus var. mongholicus and shows potent cardiovascular protective effects. In this article, we comprehensively reviewed 189 small molecules isolated from the two Astragalus species and discussed the interspecies chemical differences. Moreover, we summarized the pharmacological activities and mechanisms of action of Huang‐Qi and its major bioactive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 115 publications
(210 reference statements)
0
66
0
Order By: Relevance
“…Furthermoe, the Ligusticum chuanxiong hort (Chuanxiong) and Dalbergia odorifera (Jiangxiang) can effectively improve microcirculation and reduce blood viscosity 11 , 12 ; Astragalus mongholicus(Huangqi), Pueraria lobata(Gegen), Pseudostellaria sylvatica (Taizishen) can promote blood circulation as well. It effectively reduces the body's inflammatory response, and restores the balance between the body's coagulation system and fibrinolytic system 13 15 . In addition, the prescription also contains Ophiopogon japonicus (Maidong), fried Glycyrrhiza uralensis Fisch (Zhigancao), Allium macrostemon Bunge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermoe, the Ligusticum chuanxiong hort (Chuanxiong) and Dalbergia odorifera (Jiangxiang) can effectively improve microcirculation and reduce blood viscosity 11 , 12 ; Astragalus mongholicus(Huangqi), Pueraria lobata(Gegen), Pseudostellaria sylvatica (Taizishen) can promote blood circulation as well. It effectively reduces the body's inflammatory response, and restores the balance between the body's coagulation system and fibrinolytic system 13 15 . In addition, the prescription also contains Ophiopogon japonicus (Maidong), fried Glycyrrhiza uralensis Fisch (Zhigancao), Allium macrostemon Bunge.…”
Section: Introductionmentioning
confidence: 99%
“…3‐OH, 2′‐OH, and 6‐OH glycosylated triterpenes are commonly seen in nature [20] . For example, cycloartane‐type saponins (astragalosides) are the major bioactive constituents in the roots of Astragalus membranaceus .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we reported the first plant cycloartane‐type glycosyltransferase AmGT8 from Astragalus membranaceus , a tonic herbal medicine containing mainly cycloartane‐type saponins [20] . AmGT8 simultaneously catalyzed the 3‐OH, 6‐OH and 2′‐OH glycosylation of cycloastragenol or its 3‐ O ‐glucoside.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The TCMIs included in this study all have the effect of nourishing Qi and blood. And a large number of articles and reviews have explored the protective effects of the active ingredients of these TCMIs on cardiovascular diseases in terms of molecular mechanisms, such as Huang-Qi ( Radix Astragali ) ( Su et al, 2021 ) in HQ, the combination of Ren-Shen ( Radix Ginseng ) and Fu-Zi (processed) ( Radix Aconiti Lateralis Preparata ) ( Tan et al, 2018 ; Li L. et al, 2020 ) in SF, the combination of Hong-Shen ( Radix Ginseng Rubra ) and Mai-Dong ( Radix Ophiopogonis ) ( Wang et al, 2019 ) in SM and YQFM, Wu-Wei-Zi ( Fructus Schisandrae ) ( Nasser et al, 2020 ) in SGM, and American cockroach ( Periplaneta Americana Linnaeus ) ( Qi et al, 2017 ; Lin S. S. et al, 2019 ) in XML. Due to the available active ingredients, rich and diverse targets, and complex regulatory mechanisms, TCMIs have considerable development potential.…”
Section: Discussionmentioning
confidence: 99%